Economic sanctions in EU private international law - Szabados, Tamas ([London, England] : Hart Publishing, 2020)
"Economic sanctions are instruments of foreign policy. However, they can also affect legal relations between private parties - principally in contract. In such cases, the court or arbitration tribunal seized must decide whether to give effect to the economic sanction in question. Private international law functions as a 'filter', transmitting economic sanctions that originate in public law to the realm of private law. The aim of this book is to examine how private international law rules can influence the enforcement of economic sanctions and their related foreign policy objectives. A coherent EU foreign policy position - in addition to promoting legal certainty and predictability - would presuppose a uniform approach not only concerning the economic sanctions of the EU, but also with regard to the restrictive measures imposed by third countries. However, if we examine in detail the application of economic sanctions by Member States' courts and arbitral tribunals, we find a somewhat different picture. This book argues that this can be explained in part by the divergence of private international law approaches in the Member States."--
1. Introduction I. Economic Sanctions in Private International Law -- II. The Aim of this Book -- III. Methodology and the Scope of the Work -- IV. The Object of the Analysis: Economic Sanctions -- V. Foreign Policy and Private International Law -- VI. Adjudicative Rhetoric and Foreign Policy Considerations -- 2. The Legal Framework for Imposing Economic Sanctions -- I. The UN Sanctions Regime -- II. Economic Sanctions in Bilateral and Multilateral Treaties -- III. Economic Sanctions in EU Law -- 3. Coherence and Legal Certainty in EU Law -- I. Coherence in the External Relations Law of the EU -- II. Legal Certainty and EU Law -- 4. Economic Sanctions in Private International Law -- I. Economic Sanctions: State Intervention in Private Law Relationships -- II. Economic Sanctions as Overriding Mandatory Provisions -- III. The Treatment of Foreign Public Law in Private Law Litigation -- IV. Conclusion -- 5. Economic Sanctions as Overriding Mandatory Provisions in EU Private International Law -- I. Economic Sanctions Imposed by the Law of the Forum State -- II. Economic Sanctions of the Lex Causae III. Economic Sanctions in the Law of a Third State Other than the Lex Causae IV. Conclusion -- 6. The Judicial Practice of the Member States -- I. France -- II. Germany III. England and Wales -- IV. Assessment of the Judicial Practice of the Member States -- V. The Outcome: A Changeable European Judicial Foreign Policy -- 7. Blocking Statutes -- I. Blocking Statutes and Private International Law -- II. A Conflict of Overriding Mandatory Provisions -- 8. 'Deactivation' of Economic Sanctions? -- I. EU Economic Sanctions and Choice-of-Court Agreements II. EU Economic Sanctions and Arbitration Agreements -- 9. Possible Solutions and Conclusions -- I. Public Ordering of Contractual Relations Affected by Economic Sanctions -- II. Private Ordering of Contractual Relations Affected by Economic Sanctions -- III. The Role of Private International Law -- IV. Conclusions.
Includes index.
Includes bibliographical references.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Conflict of laws -- Sanctions -- European Union countries; Economic sanctions, European; Private international law & conflict of laws; Electronic books